2022
DOI: 10.1093/mnras/stac1061
|View full text |Cite
|
Sign up to set email alerts
|

The long-active afterglow of GRB 210204A: detection of the most delayed flares in a gamma-ray burst

Abstract: We present results from e xtensiv e broadband follow-up of GRB 210204A o v er the period of 30 d. We detect optical flares in the afterglow at 7.6 × 10 5 s and 1.1 × 10 6 s after the burst: the most delayed flaring ever detected in a GRB afterglow. At the source redshift of 0.876, the rest-frame delay is 5.8 × 10 5 s (6.71 d). We investigate possible causes for this flaring and conclude that the most likely cause is a refreshed shock in the jet. The prompt emission of the GRB is within the range of typical lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Figure 6 shows the comparison of GRB afterglow detections followed up by GIT to the Swift GRB optical afterglow population (Kann et al 2011). We see that GIT has obtained dense sampling of several GRBs (see for instance Kumar et al 2022) and that the afterglow candidates studied by GIT show similar fading characteristics as the broader sample of Swift GRBs.…”
Section: Afterglows Of Gamma-ray Burstsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure 6 shows the comparison of GRB afterglow detections followed up by GIT to the Swift GRB optical afterglow population (Kann et al 2011). We see that GIT has obtained dense sampling of several GRBs (see for instance Kumar et al 2022) and that the afterglow candidates studied by GIT show similar fading characteristics as the broader sample of Swift GRBs.…”
Section: Afterglows Of Gamma-ray Burstsmentioning
confidence: 93%
“…Another interesting GRB 210204A which showed deviations from typical synchrotron-driven afterglow emission at late times was followed up by GIT in coordination with other Indian facilities like HCT, DOT, and DFOT. A detailed study of this GRB was published in Kumar et al (2022).…”
Section: Afterglows Of Gamma-ray Burstsmentioning
confidence: 99%
“…This makes flares a common feature in GRBs despite the difference in progenitors. The majority of flares happen before a few 1000 s (Chincarini et al 2007); however, a few flares are found to occur as late as 10 6 s (Swenson et al 2010;Kumar et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Deeper optical photometric follow-up observations of energetic transients, such as afterglows of long and short GRBs are frequently carried out (Dimple et al, 2020;Kumar et al, 2021aKumar et al, , 2022Gupta et al, 2021cGupta et al, , d, e, 2022 using the recently commissioned largest Indian optical telescope, i.e., 3.6m DOT situated at Devasthal observatory of Aryabhatta Research Institute of Observational Sciences (ARIES), Nainital and the back-end instruments (Ojha et al 2018;Pandey et al 2018;Kumar et al 2021b). Observations of galaxies and other objects of low-surface brightness are also carried out using the 3.6m DOT (Kumar et al 2021b;Panwar et al 2021).…”
Section: Introductionmentioning
confidence: 99%